Elucidating the nomenclature and taxonomy of Phalaena euphemia Stoll, 1781, the type species of the genus Heraclia Hübner, [1820] (Lepidoptera, Noctuidae, Agaristinae) - Collins, Abigail H. (Zootaxa, 2021)
The genus Heraclia (Lepidoptera, Noctuidae, Agaristinae) and the species involved in the confused nomenclature and taxonomy of the type species, Phalaena euphemia Stoll, 1781 are investigated. The rediscovery of the type specimen of Noctua geryon Fabricius, 1781, a taxon that had previously been treated as the senior synonym of euphemia, justified the revival of the latter from synonymy with the former. The type material of euphemia could not be traced and a neotype is designated to fix the published name to a physical specimen. In addition to detailed diagnoses and re-descriptions, the revised taxonomy of Heraclia euphemia and Heraclia geryon is provided and the following new synonymies are proposed: Eusemia pallida Walker, 1854 and Eusemia niveosparsa Westwood, 1881 are synonymised with H. geryon and Eusemia nugatrix Westwood, 1881 is synonymised with H. euphemia. Distributional data for each of the species are presented.